Nitrogen doped CNTs supported Palladium electrocatalyst for hydrogen evolution reaction in PEM water electrolyser. (7th December 2016) - Ramakrishna, S.U.B.; Srinivasulu Reddy, D.; Shiva Kumar, S.; Himabindu, V.
Abstract: Nitrogen doped Carbon nanotubes supported Palladium electrocatalysts were synthesized and used as a hydrogen electrode in PEM water electrolyser. The Morphology and electrochemical performances of synthesized Pd/NCNTs was determined by FESEM, XRD, and cyclic voltammetry method. The Membrane electrode assemblies (MEAs) were fabricated using Pd/NCNTs and tested in PEM single cell at various experimental conditions. The results shows that the synthesized Pd/NCNTs can be promising alternative for Pt based electrocatalysts for Hydrogen evolution reaction (HER). Highlights: Nitrogen doped CNTs were prepared using chemical vapour deposition (CVD). Pd/NCNTs were successfully synthesized by chemicals reduction method. Pd/NCNTs used as electro catalyst and studied in 1 cm 2 and 25 cm 2 single PEM water electrolyser. The Pd/NCNTs could be used as alternative electrocatalyst for HER in PEM water electrolysis.